PENGARUH ORIENTASI PENEMPATAN KERJA, MOTIVASI EKSTRINSIK, DAN DIGITAL WELL BEING TERHADAP KINERJA KARYAWAN GENERASI Z DI PT WORLD INNOVATIVE TELECOMMUNICATION (STUDI KASUS PADA SPB DAN SPG OPPO DI KOTA BENGKULU) - Rizal, Aef; Lakoni, Idham; Waliamin, Janusi (Jurnal Manajemen, 2025)
This study aims to analyze the influence of job placement orientation, extrinsic motivation, and digital well-being on the performance of Generation Z employees at PT World Innovative Telecommunication (OPPO) in Bengkulu City. A quantitative explanatory approach was used to examine the relationships and influences among the variables. The population of this study consisted of 97 individuals, with the sample determined using a saturated sampling technique, resulting in a total of 97 respondents. The results of the study show that, partially, job placement orientation and digital well-being have a positive and significant effect on employee performance, while extrinsic motivation does not show a significant effect. Simultaneously, the three independent variables have a significant effect on employee performance, as indicated by an F-value of 104.297 with a significance level of 0.000. These findings indicate that appropriate job placement and a good level of digital well-being are important factors in improving the performance of Generation Z employees in a technology-based work environment